PENGEMBANGAN PERANGKAT PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA MATERI KONSEP LARUTAN DI SMK NEGERI 3 BANTAENG - Samsinar Saleh (Chemistry Education Review (CER), 2017)
This research is the development (research and development) which aims to: (1) obtain a picture of the development process of the type cooperative learning of Jigsaw valid, practical, and effective, (2) determine tinhgkat validity, practicality, and effectiveness of the cooperative learning of Jigsaw the material solution concept at SMK Negeri 3 Bantaeng. The subjects were students of class X SMK Nursing B 3 Bantaeng by the number of students 18 people in the second semester of the 2015/2016 academic year. Model development of learning tools used are 4-D models of Thiagarajan, Semmel & Semmel. The result of the development of learning tools in the form of draft RPP, Books Students (BPD) and Worksheet Students (LKPD) that can be used by teachers and students in the learning process material solution concept. The level of success in field trials demonstrated by tests of learning outcomes that achieve mastery of 100%, a positive response from the students reached 93.70% for books learners, 92.38% and 85.24% for LKPD for the learning and the learning process and keterlaksanaan learning tools are at very high criteria. based on the criteria used to assess the resulting learning device that validity, effectiveness and practicality, the learning tools developed meet the quality is good.